Chinese Guidelines for Diagnosis and Treatment of the Ehlers-Danlos Syndromes - Chinese Multi-Disciplinary Working Group on the Ehlers-Danlos Syndromes (罕见病研究, 2023)
The Ehlers-Danlos syndromes (EDS) are a group of rare hereditary connective tissue disorders. EDS is clinically and genetically heterogeneous and usually involves multiple systems. EDS has 14 subtypes, the common features of which include joint hypermobility, skin hyperextensibility, tissue fragility, and etc. The clinical manifestations and their severity differ between the subtypes, involving recurrent joint dislocations, scoliosis, arterial aneurysm and dissection, organ rupture, and others. The complexity of the disease poses challenges to the diagnosis and management of EDS, together with the rareness of the disease. The development of clinical guidelines and implementation of coordinated multi-disciplinary team (MDT) approaches to the EDS is in priority in the world.Therefore, we formed the Multi-Disciplinary Working Group on the Ehlers-Danlos Syndromes in China. Based on GRADE methodology, the MDT group developed the Guidelines. The Group highly recommends a coordinated MDT approach to the diagnosis and management of EDS. The first drafted guidelines on EDS will facilitate the shortening of the diagnostic odyssey and meeting the unmet medical needs of the patients.